Taxonomic problems surrounding Barsine orientalis bigamica Černý & Pinratana, 2009 with description of a new species (Lepidoptera, Erebidae, Arctiinae, Lithosiini) - Huang, Si-Yao; Volynkin, Anton V.; Wang, Min; Fan, Xiao-Ling (Zootaxa, 2020)
The taxonomic problems surrounding the taxon Barsine orientalis bigamica Černý & Pinratana, 2009 are preliminary elucidated. B. orientalis bigamica is raised to a specific level: B. bigamica stat. nov. Barsine kampoli Černý, 2009 syn. nov. is synonymized with B. bigamica and the true holotype of this taxon is clarified. Barsine tongi Huang & Volynkin sp. nov., a new species externally similar to B. bigamica is described from Hainan Island, S. China. The adult and genitalia of the species aforementioned and related are illustrated.